In-depth in vitro Evaluation of the Activity and Mechanisms of Action of Organic Acids and Essential Oils Against Swine Enteropathogenic Bacteria - Gómez-García, Manuel; Argüello, Héctor; Puente, Héctor; Mencía-Ares, Óscar; González, Sandra; Miranda, Rubén; Rubio, Pedro; Carvajal, Ana (Frontiers in Veterinary Science, 2020)
Alternative antimicrobials require a deep understanding of their action mechanisms by in vitro assays which support science-based field use. This study focuses on the characterization of bactericidal mechanisms of potential antimicrobial compounds, two organic acids and three single essential oil (EO) compounds against swine enteropathogenic bacteria Escherichia coli, Salmonella enterica subsp. enterica serovar Typhimurium and Clostridium perfringens. Target concentrations of the compounds were evaluated using the inhibitory potential of the vapor phase and bacterial viability after short-term exposure, while cell targets were disclosed using flow cytometry (FC), Fourier-transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). All tested compounds exhibited vapor phase activity against the three bacterial species, except sodium salt of coconut fatty acid distillates against C. perfringens. Survival test results evidenced that effects on bacterial viability were concentration dependent and higher in single EO compounds than in organic acids. In detail, thymol and its isomer carvacrol were the most effective compounds. Further characterization of thymol and cinnamaldehyde activity revealed that thymol main target was the cell membrane, since it caused striking damages in the membrane permeability, integrity and composition evidenced by FC and FTIR in the three enteric pathogens. In contrast, cinnamaldehyde was more effective against enterobacteria than against C. perfringens and only caused slightly damages at the highest concentration tested. Its target at the molecular level differed between enterobacteria and C. perfringens strains. The SEM micrographs allowed us to confirm the results previously obtained for both EO compounds by other techniques. Altogether, the study showed the straight effect of these antimicrobials, which could constitute relevant information to optimize their feed inclusion rates in field studies or field use.